SmartDR: algorithms and techniques for fast detailed routing with good design rule handling - Gonçalves, Stephano Machado Moreira (2020)
Submitted by Aline Batista (alinehb.ufpel@gmail.com) on 2020-08-11T21:36:07Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Tese_Stephano_Machado_Moreira.pdf: 3252235 bytes, checksum: 16f91f7fc566bd22ffa09aa59c0d5b72 (MD5)